Translation of Culture - Embedded pieces : A study on a select piece of religious Psalm, Thiruppugazh - Gayathree, S. (University of Jaffna, 2017)
Translation is a noble task of transferring the substance from one language to another. As translation is an emerging field with vigorous efforts, it is a need of the time to discern and analyse the practices, methods, approaches and techniques employed during the process in order to meet the satisfaction of the target readership. There has been a question regarding the transference of a culture-embedded piece for an alien target group who are not aware or acquainted with the source culture. It is inevitable to analyse whether itis possible to maintain a balance between the loyalty to the original and the satisfaction of the target readership. Thus, this research gets its significance. Bringing out the exactness and originality with fidelity sometimes needs the employment of some methods like paraphrasing and interpreting based on cultural connotations and mythological allusions together with the techniques, strategies and crafts. In this research Psalm Thiruppugazh 'VWkapy; VwptpisahL Kfk; xd;Nw ...' has been translated. As each line of this Psalm carries cultural connotations and mythological allusions, it is not possible for an alien reader to comprehend the real meaning or real implication lies in each line without understanding the cultural connotation and mythological allusions in respective contexts. This study aims at the strategies utilized to meet the satisfaction of the target readership through the translation of the Psalm 'ஏறுமயில் ஏறிவிளையாடு முகம் ஒன்றே ...'. The budding translators may be facilitated by acquiring this knowledge. Application of this may enrich the performance.
Keywords: Cultural Connotation; Mythological Allusion; Originality; Strategies